Tailoring poly(butylene 2, 5-thiophenedicarboxylate) features by the introduction of adipic acid co-units: Biobased and biodegradable aliphatic/aromatic polyesters. (6th June 2018) - Guidotti, Giulia; Gigli, Matteo; Soccio, Michelina; Lotti, Nadia; Salatelli, Elisabetta; Gazzano, Massimo; Siracusa, Valentina; Munari, Andrea
Abstract: A class of eco-friendly copolyesters based on poly(butylene 2, 5-thiophenedicarboxylate) (PBTF) is presented. The main goal of the study was to enhance the biodegradation rate of PBTF homopolymer. To this purpose, aliphatic sequences based on adipic acid have been introduced in the macromolecular backbone. The synthesized polymers have been characterized from thermal and structural point of view and their properties have been compared to those of the two homopolymers, i.e. PBTF and poly(butylene adipate). The peculiar microstructure of PBTF, due to the presence of an uninduced 2D-ordered phase, i.e. meso -phase, impacted also the copolymers' behavior, e.g. causing an increase of the materials' stiffness. Biodegradation rate in compost increased with the increase of mobile aliphatic sequences that allowed for an easier access to the ester bonds by the enzymes responsible for chain depolymerization. Lastly, gas permeability resulted strictly dependent on copolymer composition. Copolymers rich in thiophenedicarboxylate co-units displayed a gas barrier behavior comparable to poly(ethylene furanoate), while with the increase of adipate content the permeability increased, remaining however competitive with respect to that of polyolefines and polylactic acid. Graphical abstract: Image 1 Highlights: A class of copolymers of poly(butylene 2, 5-thiophenedicarboxylate) is presented. Aliphatic/aromatic copolyesters containing adipate subunits have been syntesized. Copolymer characteristics can be tailored by acting on molar composition. Adipate subunits impart flexibility and increase biodegradation rate. Thiophenedicarboxylate subunits play a major role in improving gas barrier properties.